Analisis Pengendalian Kualitas Menggunakan Statistical Process Control untuk Mengurangi Produk Cacat pada Mebel UD Sadewo Jagat di Ngawi - Indah Safitri; Sunarso Sunarso (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
UD Sadewo Jagat is a company engaged in furniture production, this company provides sales of finished, semi-finished products and maintenance for various types of teak wood furniture. Finished products include tables, chairs, shelves and various other types of displays. However, in this study, we only analyzed defective products for wooden box table products because the production process of wooden box table products because the production process of wooden box tables experienced problems, namely the number of defects exceending 5% of the company’s standard provisions. The aim of this research is to analyze product quality control techniques using the Statistical Process Control method in reducing defective products, and to find out what factors cause defects in products produced by UD Sadewo Jagat. This research uses the Statistical Process Control (SPC) method, which is one of the analytical methods used to analyze the causes of defects that occur, both in terms of product quality and in terms of the quality of the production process. Quality control analysis is carried out using. The results of the check sheet analysis show an average of 9,6% product defects per month. From the results of the Pareto diagram, it can be seen that the highest level of defects is crack defects, with a total of 80 units or 44,94% of total product defects in 2023. Meanwhile, the results of the control chart that has been made can be seen that quality control is uncontrolled and not according to standards. From the results of the fishbone diagram, it is concluced that the factors causing product defects are human factors, materials, environment, and methods.